Anti‐doping analytes in serum: A comparison of SST and SST‐II Advance blood collection tubes. Issue 7 (8th May 2019) - Miller, Geoffrey D.; Cox, Holly D.; Nair, Vinod; Eichner, Daniel
Abstract: Serum insulin‐like growth factor‐1 (IGF‐1), procollagen type III N‐terminal peptide (PIIINP), and human growth hormone (hGH) isoforms were analyzed in identical serum samples collected into BD Vacutainer ® SST and BD Vacutainer ® SST‐II Advance serum separator tubes. Comparing the serum collected into each tube, measurement correlation was high (R 2  > 0.83) and percent bias was minimal (<|3.2%|) for all analytes measured using World Anti‐Doping Agency (WADA)‐approved tests. As such, it is recommended that both SST and SST‐II Advance tubes can be used interchangeably for anti‐doping purposes. Abstract : Serum IGF‐1, PIIINP, and hGH isoforms were analyzed in identical serum samples collected in SST and SST‐II blood collection tubes. Measurement correlation was high and bias was minimal across the analytes. Both tube types are suitable for serum analyte analysis for anti‐doping purposes.